Hantavirus-induced disruption of the endothelial barrier: neutrophils are on the payroll - Schönrich, Günther; Krüger, Detlev H.; Raftery, Martin J. (Frontiers in Microbiology, 2015)
Viral hemorrhagic fever caused by hantaviruses is an emerging infectious disease for which suita-ble treatments are not available. In order to improve this situation a better understanding of han-taviral pathogenesis is urgently required. Hantaviruses infect endothelial cell layers in vitro with-out causing any cytopathogenic effect and without increasing permeability. This implies that the mechanisms underlying vascular hyperpermeability in hantavirus-associated disease are more complex and that immune mechanisms play an important role. In this review we highlight the lat-est developments in hantavirus-induced immunopathogenesis. A possible contribution of neutro-phils has been neglected so far. For this reason, we place special emphasis on the pathogenic role of neutrophils in disrupting the endothelial barrier.